Metacognition: A Tool to Promote an Inclusive Classroom Environment for Students with Disabilities - Vázquez-Chaves, Ana Patricia (2015)
This essay presents metacognition as a tool to promote a classroom environment inclusive for students with disabilities. It aims at promoting reflection on the methodology to address diversity within the classroom, considering the population with disabilities as one of the major groups to bear in mind. Within the conceptual approach, inclusive education is seen as the way to address diversity in the Costa Rican education system, where education is considered a fundamental human right. The Ministry of Public Education of Costa Rica is moving from a rehabilitative approach to an inclusive education approach. Metacognition is a way to raise awareness on the pedagogical mediation within the classroom environment. This paper includes results from a series of descriptive and qualitative studies conducted at Universidad Nacional, Costa Rica, which demonstrate that many of the difficulties presented in the student population are due to methodological aspects and an inadequate delivery of the contents by the teachers. The methodology used helps us to understand the ways in which students perform the cognitive processes through metacognitive strategies. It is concluded that the teaching strategies proposed to meet the educational needs comprehensively is fundamental for achieving inclusive educational processes.